Microstructures and wear properties of CoCrFexNi ( x = 0, 1) medium-entropy alloy coatings prepared by laser cladding - Yinghu Wang; Zhiyuan Wang; Jianyan Xu (Industrial Lubrication and Tribology, 2024)
Purpose High-nitrogen steel is a common material for the manufacture of drilling equipment such as drill collars. However, its poor surface properties often limit its applications. The purpose of this paper is to find a way to enhance the surface performance of high-nitrogen steel, which is expected to improve the wear resistance of high-nitrogen steel. Design/methodology/approach The CoCrNi and CoCrFeNi medium-entropy alloy (MEA) coatings were prepared on high-nitrogen steel substrate by laser cladding technology. The microstructure, phase composition and element distribution of the fabricated coatings were investigated using scanning electronic microscopy, electron backscatter diffraction and X-ray diffraction. The phase structure, phase stability and structural stability of the CoCrNi and CoCrFeNi MEAs were investigated in combination with phase diagram calculation and molecular dynamics. Then the wear tests were carried out for coatings. Findings The results show that both prepared MEA coatings have good quality and contain a single face-centered cubic phase. The wear performance of MEA coatings is improved by the refinement of grain size and the increase of dislocation density. Due to the addition of Fe atoms, the lattice distortion of the CoCrFeNi system increased, resulting in a higher dislocation density of the coating. Cr atoms in the CoCrFeNi system are the largest, and the local lattice distortions induced by them are greater. Through this study, MEA coatings with high hardness can be expanded to drilling field applications. Originality/value CoCrFeNi and CoCrNi MEA coatings were successfully prepared on the surface of high-nitrogen steel for the first time without obvious defects. The micromorphology and grain orientation of the different kinds of coatings were discussed in detail. The hardness-strengthening mechanism and structure stability of the coatings were illustrated by experiments and molecular dynamics simulations. Peer review The peer review history for this article is available at: https://publons.com/publon/10.1108/ILT-04-2024-0116/